2010
DOI: 10.4154/gc.2010.03
|View full text |Cite
|
Sign up to set email alerts
|

Palaeowind estimation of cross-bedding within the aeolian Kurkar layers of the Gaza Formation, Gaza Strip, Palestine

Abstract: Coastal plain deposits of the Gaza Strip have been distinguished in the Gaza Formation (Pleistocene) of the Kurkar Group. The Kurkar layers (medium to coarse-grained calcareous sandstone) are characterized by abundant crossbedding that has two sets of cross-beds. These Kurkar layers form the ridges along the Mediterranean coast. The dip, and dip direction of the cross-beds, were measured at fi ve sites to determine the palaeowind direction. The palaeowind directions were measured for the fi rst time in the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…However, at the Mrzeżyno dunefield, the southern and northern zones have very different strata dip directions, with a difference in the mean values of 58° (144° in the northern and 86° in the southern zone). A similar distribution of dip directions was reported from Late Pleistocene coastal aeolianites in the Gaza Strip, Palestine by Zaineldeen (), where strata inclination changes both laterally over a 1‐km distance from the coast as well as vertically indicating that the wind pattern changes with the distance from the shoreline (marine transgression).…”
Section: Interpretation and Discussionsupporting
confidence: 80%
“…However, at the Mrzeżyno dunefield, the southern and northern zones have very different strata dip directions, with a difference in the mean values of 58° (144° in the northern and 86° in the southern zone). A similar distribution of dip directions was reported from Late Pleistocene coastal aeolianites in the Gaza Strip, Palestine by Zaineldeen (), where strata inclination changes both laterally over a 1‐km distance from the coast as well as vertically indicating that the wind pattern changes with the distance from the shoreline (marine transgression).…”
Section: Interpretation and Discussionsupporting
confidence: 80%
“…The luminescence-dated (65 ka) aeolianites in the Palestine (Kurkar ridges) at the Levant (Frechen et al, 2002) have been interpreted as representing typical dunes formed simultaneously along the coastline by a perpendicular (southwest) to the shoreline wind direction. Field observations in another study from Gaza (Zaineldeen, 2010) also showed that cross-beds within the Kurkar layers were deposited by a westerly and southwesterly palaeowind.…”
Section: Age Estimates and Discussionmentioning
confidence: 87%